Bančništvo na začetku gospodarske reforme 1965 - Matjašič, Marjan (Zgodovinski časopis, 1985)
The purpose of the reformed banking system in 1965, after abolishment of the social investment funds, was not as much reorganization of the banking system as "reestablishment of new relations in the process of social reproduction..., in which the interests of the economy would dominate"; all this of course in accordance with the ideal conceptions, repeatedly exposed on the 8th Congress of the League of Communists of Yugoslavia, as well as with the aims of the economic reform, which officially began to be realised in July 1965, with some measures, however, in fact a year before.
Keywords: bančništvo; Slovenija